Sensory Experience and Sound Marketing – The Motivation of the Use of Music in Commercial Premises and Its Consequences On Consumer Behavior - Sánchez-Crespo, Isidro; Carrasco-Santos, María Jesús (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The study of the motivation for the use of advanced background music control systems and the fact of creating a good environment, a good experience for the customer who enters a place to make a purchase due to the attraction generated by the music is the object of this research. The study of the emotions derived from the use of music in commercial premises and the repercussion it has on the consumer’s purchasing behavior will be analyzed with the study of several success stories on this issue.